Heat stroke dysfunctions: from pathophysiology to prediction - Alawad, Azza; Merghani, Tarig; Yousif, Nadia; Satti, Shahenaz; Edris, Alhiedi; Hakim, Alwaleed; Fadelelmoula, Tarig (Frontiers in Physiology, 2025)
Heat stroke is a severe, life-threatening medical emergency defined by an elevation in core body temperature exceeding 40.0 °C, accompanied by acute central nervous system (CNS) dysfunction and often complicated by multi-organ failure. Although traditionally viewed as a thermoregulatory collapse from environmental exposure or intense exertion, recent evidence highlights its complex, multifactorial pathophysiology. This includes systemic inflammation, immune dysregulation, oxidative stress, endothelial injury, and activation of the coagulation cascade. This comprehensive narrative examines advances in understanding underlying mechanisms, clinical manifestations, emerging biomarkers, and outcomes in both classic (non-exertional) and exertional heat stroke. Emphasis is placed on the gut–brain axis, where disruption of intestinal barrier integrity and microbiota dysbiosis amplify systemic inflammation and contribute to neurotoxicity. Heat stroke-related neurological damage affects critical brain regions, including the hypothalamus, cerebellum and hippocampus, often resulting in long-term cognitive and motor impairments. Several biomarkers that include interleukin-6 (IL-6), high-mobility group box 1 protein (HMGB1), creatine kinase (CK), S100β, and D-dimer are under active investigation for diagnostic and prognostic utility, but their clinical use remains limited by inter-individual variability and lack of standardized thresholds. Recent advances in artificial intelligence (AI) and wearable biosensors may facilitate early detection, continuous monitoring, and individualized risk prediction, particularly in vulnerable populations such as outdoor workers, athletes, and military personnel. An interdisciplinary approach is critical to improving early recognition, management strategies, and long-term outcomes in the context of rising global temperatures and climate change.